Inefficiencies in coupled electricity markets with different time granularity: Exploring the zigzag pattern - Christopher Jahns (University of Duisburg-Essen, House of Energy Markets & Finance (HEMF), 2024)
In European intraday electricity markets, a systematic zigzag pattern can be observed, characterized by alternating maxima and minima at the shift of hourly products. This price formation contradicts the fundamental understanding, that prices to are a monotonously increasing function of residual demand and correspondingly would evolve smoothly across hours. This study investigates the phenomenon of restricted participation as the primary cause of the zigzag pattern. Restricted participation occurs when market participants maintain constant output through subhourly products. A notable instance is the lack of sub-hourly cross-border trading where foreign market participants are restricted from engaging in trading sub-hourly products. This is closely linked to is the differing time granularities observed in electricity trading across European countries. Three research questions guide this investigation: (1) Is restricted participation the main cause of non-smooth intraday prices? (2) How do technical restrictions on cross-border trading contribute? (3) What role do ramping and start-up costs play? Utilizing regression models and openly available data from Germany, the research confirms that restricted participation is the primary cause of the zigzag pattern. Furthermore, an analytical model of restricted participation in cross-border trading is developed, along with empirical parameterization. Based on this model it is estimated that lifting all technical restrictions on trading sub-hourly products would reduce systematic non-smoothness in intraday prices by only about 27%. These findings are unexpected, suggesting that despite economic incentives, a significant number of domestic power plants do not adjust their output based on intraday price signals. Ramping and start-up costs appear to have little influence.
Keywords: C10; C54; Q41; 330; Intraday electricity market; Econometric modeling; Market coupling